Foundations of Software Science and Computation Structures: 21st International Conference, FOSSACS 2018, Held as Part of the European Joint Conferences on Theory and Practice of Software, ETAPS 2018, Thessaloniki, Greece, April 14-20, 2018. Proceedings - Baier, Christel; Dal Lago, Ugo (Theoretical Computer Science and General Issues, 2018)
artificial intelligence; computer software; selection and evaluation; formal logic; graph theory; modal logic; petri nets; program compilers; programming language; semantics; separation logic; software engineering; theorem proving; type systems; verification